Polarization or bridging? Responses of Muslim and non-Muslim organizations to criticism of Islam in the Netherlands - Vellenga, Sipco J. (Islam and Christian-Muslim relations, 2013)
Since the beginning of the twenty-first century, Islam has been a target of harsh criticism in the Netherlands, as in many other European countries. This article examines and analyses the way leaders of 10 Muslim and 11 non-Muslim organizations responded to criticism of Islam in the Netherlands in the period 2004-10. The focus is on the response to five episodes: the film Submission (2004), the Danish Cartoon Affair (2005-2006), the film Fitna (2008), the Internet film An interview with Mohammed (2008) and the Swiss ban on the building of minarets (2009). Several specific patterns of response are noted. The responses of Muslim organizations vary from resignation to defensive to offensive, and those of non-Muslim organizations from supportive to critical. These patterns are strongly linked to the organizations' leaders' framing of the situation, including the incidents themselves and other organizations, and their own mission and strategy, as well as, in the case of Fitna, to the policy of the Dutch government. All the organizations researched reject extreme forms of polarization and the mainstream Christian, Islamic and Jewish organizations in particular have strengthened their mutual ties in response to expressions of criticism of Islam.